2017
DOI: 10.11648/j.ajns.20170605.12
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Expectations and Evaluations of Mentors’ Competences and Mentors’ Self-Evaluations as Indicators of Mentoring Process Quality

Abstract: Important information about the clinical education can be revealed by nursing students' initial expectations and final evaluation of mentors' competences, and mentor's self-evaluation of their competences. The aim of this study was to examine whether these constructs can be used for evaluating the atmosphere in clinical education. This was a nonexperimental prospective study. Data were collected between January and April 2012, in 12 clinics at the University Hospital Osijek. The participants were undergraduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 14 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…This directive defines that during the course of a three-year study and a minimum of 4,600 hours, Bachelor of Science (BSc) nursing students in Croatia should spend at least 2,300 hours in a clinical environment under the supervision of a clinical mentor with a BSc and who is a qualified Registered Nurse (RN). 4,5 Despite implementation of the EU directive, the mentoring system in the Republic of Croatia has not experienced significant changes. CT is mainly organized as a group mentoring approach, in which an individual approach to each students' needs is not possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This directive defines that during the course of a three-year study and a minimum of 4,600 hours, Bachelor of Science (BSc) nursing students in Croatia should spend at least 2,300 hours in a clinical environment under the supervision of a clinical mentor with a BSc and who is a qualified Registered Nurse (RN). 4,5 Despite implementation of the EU directive, the mentoring system in the Republic of Croatia has not experienced significant changes. CT is mainly organized as a group mentoring approach, in which an individual approach to each students' needs is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…6 A relevant indicator for the importance of the topic being researched is the fact that students spend a large number of hours with their mentor, during which they develop a relationship that is a key element in their satisfaction. 5,7 The literature shows that the satisfaction of nursing students with their mentors is a frequently investigated topic around the world. 1,7-10 However, there is a lack of research and insufficient comparisons of students' perceptions of the mentor-student relationship in relation to different mentoring approaches such as individual, dual, or group mentoring in CT.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 22 ] However, Lovrić et al . (2017)[ 16 ] in Croatia found that the mean effectiveness of clinical educators' teaching behaviors in the second and third academic years had been statistically higher than that in the first one. The mentioned studies in different regions produced very different estimates about such behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned studies in different regions produced very different estimates about such behaviors. [ 16 20 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation